A bioecological view of interracial/same-race couple conflict. Issue 3 (8th July 2014) - A. MacNeil, Theresa; Adamsons, Kari
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose if this study is to examine differences in conflict management strategies, relational satisfaction and social support of individuals in same-race and interracial relationships. Additionally, the authors examined associations between self-reported and observed measures of conflict management strategies. Design/methodology/approach – The current study used Bronfenbrenner's (2005) bioecological theory as an organizing framework. Twenty individuals in interracial and same-race relationships were recruited from a large Northeastern US university. Self-report and observational measures of conflict management strategies were obtained as were individuals' self-reported levels of relational satisfaction and social support. Findings – Results indicated a few differences in conflict management strategies between individuals in same-race and interracial dyads and no differences in social support or satisfaction. Observational measures of conflict management were largely uncorrelated with their corresponding self-report measures. Research limitations/implications – The current sample was small and consisted of students from a predominately White region of the country; thus generalizability and statistical power are limited. However, the results suggest ways interracial and same-race dyads might manage conflict differently as well as how self-reported and observational methods might differ in terms of the results obtained. Originality/value – Interracial couple relationship processes are largely unexplored, but are important to study. The current findings further suggest that self-report and observational methods should be combined to more fully portray the conflict management strategies of individuals in interracial and same-race relationships.